(untitled) (Bangladesh Journal of Botany, 2019)
To understand the distributions of paclitaxel and its precursors in the different parts of yew this study was conducted. The contents of paclitaxel and its precursors in the different parts of Taxus wallichiana var. mairei were determined with RP-HPLC. The contents of paclitaxel and its precursors in yew root are higher than those in other parts. The content of paclitaxel in the bark of Taxus wallichiana var. mairei is higher than that in leaf. But there was very little paclitaxel in the xylem and tender stem of Taxus wallichiana var. mairei. There were considerable paclitaxel precursors in the leaf of Taxus wallichiana var. mairei, but low contents in 2 - 3 years stem. The root of Taxus wallichiana var. mairei can be utilized also. It is reasonable measures of satisfying the demand of people on paclitaxel and preventting people cutting yew that artificially synthesize paclitaxel with the precursors extracted from yew leaf.